PENGARUH LATIHAN RANGE OF MOTION (ROM) TERHADAP PERUBAHAN SKALA NYERI PADA LANSIA DENGAN OSTEOARTRITIS DI POSYANDU LANSIA DESA KALIANGET TIMUR KECAMATAN KALIANGET KABUPATEN SUMENEP - Mujib Mujib; Emdat Suprayitno (Journal Of Health Science (Jurnal Ilmu Kesehatan), 2016)
Background: Osteoarthritis is a degenerative joint disease in which damage to the joints of aging been anticipated plays an important role in the development of osteoarthritis (Stanley, 2006). It forced a decline in activity or immobilization so it accelerate the prognosis of the disease. This study aimed to determine the Range of Motion (ROM) exercise influence in changing the pain scale in elderly with osteoarthritis in the elderly Posyandu Kalianget Timur Kalianget Sumenep. Method: This Research design is pre experiment one group pre and post test design with simple random sampling. The population are 76 people with total sample of 64 people. Data were analyzed using wilcoxon test. Result: The results of the study prior to Range of Motion (ROM) exercise pain scale at nearly half the respondents (48.4%) had moderate pain (scale 4-6). And after Range of Motion (ROM) exercise pain scale at nearly half the respondents (46.9%) had mild pain (scale 1-3). Data were analyzed using wilcoxon test. The results obtained p = 0.000 which means Range of Motion (ROM) exercise significantly effective in changing the pain scale in osteoarthritis patients in the elderly Posyandu Kalianget Timur Sumenep. Conclusion: ROM exercises is non pharmacological therapy that can aplied to reduce the scale of pain in elderly with osteoarthritis. The result of this study is expected to increase the knowledge and prevent pain by creating and ROM maintaining positive habit to avoid degenerative joint stiffness that caused by pain.